KEY TRENDS IN THE DEVELOPMENT OF MARKETPLACES AS A TRIGGER FOR THE TRANSFORMATION OF GLOBAL BUSINESS - Mietule, Iveta; Maksymova, Irina; Holikova, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
This research analyses marketplaces in Europe and some other developed countries in order to determine their impact on global trade and business. The paper aimed to answer an important question - how e-commerce could transform modern business taking into account digital changes, a boom of cryptocurrency erasing trade borders and globalization. Sufficient evidence of this transformation is illustrated. A subsidiary objective of this research involves the building of a logical model describing correlation between marketplaces as integral part of e-commerce and global business development. Statistical data were based on variable indicators describing four categories of trading platforms, particularly online stores, price aggregators, marketplaces and classifiers. In addition, global indexes and macro-economic criteria were used in analysis. The methodology of statistical and regression methods was employed for economic-mathematical modelling. This allowed revealing the most important indicators affecting e-commerce and to create reasonable predictions for global business and trade. The research highlights important trends in the development of e-business under the digital economy.